New media, performative violence, and state reconstruction in Mogadishu. Issue 468 (27th April 2018) - Chonka, Peter
Abstract: Since 2012, Mogadishu has been the site of both unprecedented optimism around the reconstruction of the Somali state, as well as persistent violence perpetrated by the Islamist militants of Harakat Al Shabaab Al Mujahidiin (Al Shabaab). In attacking hotels and restaurants, as well as other sites broadly associated with the state, Al Shabaab has prosecuted a strategy intended to foment the un-governability of the city, undermine the nascent Federal Government of Somalia's claims to authority, and denounce the alleged 'foreign' capture of the re-emerging state. Based on discursive analyses of local political commentary, and fieldwork in Mogadishu, this article examines media contestation between the re-emerging state and the armed opposition in a context of prolonged political fragmentation. The article argues that not only does the highly decentralized and transnational modern media environment facilitate a dynamic and dialogic exchange of propaganda between the state and the insurgents but, furthermore, the technological context of this discursive contestation has important implications for the ways in which counter-terrorism and state reconstruction are undertaken by political and military actors on the ground.